Sistem Pendukung Keputusan untuk Pemilihan Sepeda Motor bagi Mahasiswa dengan Menggunakan Metode Simple Additive Weighting (SAW) - Anggit Suryan Rohyan; Satria Fajar Dwi Kurniawan; Hendra Maulana; Nor Anisa (Jurnal Riset Sistem dan Teknologi Informasi, 2025)
Researchers conducted a selection process for motorcycles that align with the needs and financial conditions of students, as this process is often quite complex. This complexity arises from the wide range of options and the numerous criteria that must be considered, such as price, fuel efficiency, engine capacity, comfort level, and design aesthetics. The objective of this study is to design a Decision Support System (DSS) by implementing the Simple Additive Weighting (SAW) method to assist students in selecting the motorcycle that best fits their needs. The SAW method was chosen due to its effectiveness in handling multi-criteria decision-making problems by assigning weights to each criterion and calculating the preference value for each available alternative. The system was developed using a quantitative approach, with data collected through surveys and documentation of motorcycle specifications. The test results indicated that the system was capable of providing accurate and relevant recommendations based on user needs. Therefore, this system has the potential to serve as an effective tool in supporting students' motorcycle selection decisions.